PENYULUHAN PADA IBU PENGETAHUAN TENTANG PENTINGNYA PENYEGAHAN STUNTING SEJAK DINI DI POSYANDU LAVENDA WILAYAH KERJA PUSKESMAS KENALI BESAR KOTA JAMBI - Mastikana, Indah; Nadya, Embun; Lestari, Dewi Lestari; Rahmadiyanti, Noprinta; Madona, Yara Octari (Transpublika Publisher, 2023)
Child stunting is a condition of chronic malnutrition that occurs due to long-term inadequate food intake. Stunting not only affects physical growth, but also becomes a problem that makes children more vulnerable to infection. One of the causes of stunting is a lack of maternal knowledge. Maternal understanding of child nutrition is very important in preventing stunting. Based on data fro the Ministry of Health announced the results of the Indonesian Nutrition Status Survey (SSGI) at the BKKBN National Work Meeting, where the prevalence of stunting in Indonesia fell from 24.4% in 2021 to 21.6% in 2022. The purpose of this activity is to increase public knowledge in preventing stunting as early as possible. The method used in this activity was carried out during the implementation of community service by counseling the local community at Posyandu Lavenda in the working area of the Kenali Besar Health Center, Jambi City. Based on the results of these activities, all participants were very enthusiastic about the counseling and proactive health workers took preventive actions related to the causes of stunting and prevent stunting in children as early as possible.